Mechanical engineering design - Shigley, Joseph Edward (McGraw-Hill series in mechanical engineering, 2004)
The seventh edition of Mechanical Engineering Design marks a return to the basic approaches that have made this book the standard in machine design for over 40 years. At the same time it has been significantly updated and modernized for today's engineering students and professional engineers. Workin